Dataset from: Highly purified and functionally stable in vitro expanded allospecific Tr1 cells expressing immunosuppressive graft-homing receptors as new candidates for cell therapy in solid organ transplantation - Arteaga-Cruz, Saúl (2023)
The development of new strategies based on the use of Tr1 cells has taken relevance to induce long-term tolerance, especially in the context of allogeneic stem cell transplantation. Although Tr1 cells are currently identified by the co-expression of CD49b and LAG-3 and high production of interleukin 10 (IL-10), recent studies have shown the need for a more exhaustive characterization, including co-inhibitory and chemokines receptors expression, to ensure bona fide Tr1 cells to be used as cell therapy in solid organ transplantation. Moreover, the proinflammatory environment induced by the allograft could affect the suppressive function of Treg cells, therefore stability of Tr1 cells needs to be further investigated. Here, we establish a new protocol that allows long-term in vitro expansion of highly purified expanded allospecific Tr1 (Exp-allo Tr1). Our expanded Tr1 cell population becomes highly enriched in IL-10 producers (> 90%) and maintains high expression of CD49b and LAG-3, as well as the co-inhibitory receptors PD-1, CTLA-4, TIM-3, TIGIT and CD39. Most importantly, high dimensional analysis of Exp-allo Tr1 demonstrated a specific expression profile that distinguishes them from activated conventional T cells (T conv), showing overexpression of IL-10, CD39, CTLA-4 and LAG-3. On the other hand, Exp-allo Tr1 expressed a chemokine receptor profile relevant for allograft homing and tolerance induction including CCR2, CCR4, CCR5 and CXCR3, but lower levels of CCR7. Interestingly, Exp-allo Tr1 efficiently suppressed allospecific but not third-party T cell responses even after being expanded in the presence of proinflammatory cytokines for two extra weeks, supporting their functional stability. In summary, we demonstrate for the first time that highly purified allospecific Tr1 (Allo Tr1) cells can be efficiently expanded maintaining a stable phenotype and suppressive function with homing potential to the allograft, so they may be considered as promising therapeutic tools for solid organ transplantation.